Entre air et terre : les éléments dans Aurora Leigh d’Elizabeth Barrett Browning - Marianne Camus (Cahiers Victoriens et Edouardiens)
Surprisingly enough, despite the fact that it is strongly associated with femininity, Elizabeth Barrett Browning has no use for water as an element in her narrative of Aurora Leigh’s progress as a poet in the eponymous poem. Fire is only used in its usual purifying function, for the male protagonist. But she does construct a complex architecture from the elements of earth and air. She starts with the generally accepted duality of earth, both nurturing and a symbol of death. She multiplies the associations with air : angels and squirrels, wind and mountains, to cite only a few. She then examines and redefines the relationships between these two elements in life and in poetry and finally reaches a mystical union anchored in the body.